STUDI KEMAMPUAN MENULIS PANTUN NASIHAT SISWA KELAS IVA SD NEGERI 73 KOTA BENGKULU - Daimun Hambali; Ansyori Gunawan; Tesy Ratnasari (Universitas Bengkulu, 2018)
This study aims to analyze the ability to write pantun advice class IVA SD Negeri 73 Bengkulu City. The type of this research is quantitative descriptive research. Research subjects amounted to 21 students. The research instrument is a test sheet. Technique of collecting data in the form of test. Data analysis technique is done with simple statistical calculation. From the data analysis show that 1) conformity with criteria of rhyme including excellent category with average percentage of 86%, (2) attractiveness of pantun contents including enough category with average percentage 72,6%, (3) power of imagination including enough category with average Percentage 65.4%, (4) accuracy of diction and spelling including enough category with average percentage 67,8%, and (5) theme renewal including enough category with average percentage 67,8%. Details of pantun's advice writing skills are: no students included in either category, 7 students included in either category, 13 students included in enough category, 1 student included in the category less. With an average overall percentage of 67.2% with sufficient category. Thus it can be concluded that 12 students are capable and 9 students are not able to write pantun advice.